Does gender discrimination in social institutions matter for long-term growth? Cross-country evidence - Ferrant, Gaëlle (OECD Publishing, 2016)
This paper estimates the potential income gains associated with greater gender parity in social institutions and the cost of the current level of discrimination. Using cross-country analysis, it investigates how gender-based discrimination in social institutions, measured by the OECD Development Centre's Social Institutions and Gender Index (SIGI), affects income per capita. First, the empirical results indicate that such discrimination impedes a country's level of income beyond its effect on gender inequality in outcomes. Second, the effect is stronger for lowincome countries. Third, the channel decomposition analysis indicates that gender-based discrimination in social institutions tends to reduce income per capita by lowering both women's human capital acquisition and labour force participation, as well as total factor productivity. Fourth, the income loss associated with gender discrimination in social institutions is estimated at up to USD 12 trillion, or 16% of world income. By contrast, a gradual dismantling of genderbased discriminatory social institutions by 2030 could increase the annual income global growth rate by 0.03 to 0.6 percentage points over the next 15 years, depending on the scenario. Such results are robust to changes in specifications and controls for potential endogeneity
Keywords: Employment; Social Issues/Migration/Health; Development; Economics